Characteristics of Farmer Adopters of High Value Horticultural Crops in Indonesia - Suprehatin Suprehatin (School of Business, Bogor Agricultural University (SB-IPB), 2019)
Improving the participation of smallholder farmers in horticultural value chains to benefit from the rapidly growing demand for high value agricultural products is one strategy for raising farm income. However, smallholder farmer adoption of high value horticultural crops in Indonesian is under-researched. To address this knowledge gap, this study aims to examines the characteristics of farmers who adopted and those who did not adopt a new horticultural crop with respect to the household (farmer), farm and institutional characteristics. The unique data from a 2013 survey of 960 Indonesian farmers on Java Island that produce a variety of agricultural products was analysed using independent-sample t-tests. Basic statistical analysis showed relatively low adoption rates (10%) of new horticultural crops amongst 960 selected Indonesian farmers with different characteristics. The result showed that current low rates of horticultural crop adoption are associated with a variety of factors, such as lower levels of education among farmers, resource constraints, lack of information on horticultural crop production and low participation in farmer groups.Keywords: horticultural crops, smallholder farmer adoption, household